EVALUASI AKTIVITAS ANTIBAKTERI SABUN VCO pH NETRAL TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Dwi Cahyanti, Naomi; Whisnu Trie Seno Ajie (Jurnal Insan Farmasi Indonesia, 2025)
Liquid bath soap is widely used as an antiseptic in daily activities, but its generally high pH can erode the skin’s protective barrier and reduce comfort. Saponification is the reaction between a strong base and fatty acids. Virgin Coconut Oil (VCO), which contains lauric acid, is known for its antibacterial properties. This study aimed to determine the characteristics of VCO-based liquid soap and compare its antibacterial effectiveness against two structurally different bacteria, Staphylococcus aureus and Escherichia coli. The research employed a post-test only experimental design with descriptive-quantitative data collection. The stages included organoleptic evaluation, pH measurement, viscosity, specific gravity, and foam height testing. Only samples that fulfilled standard soap characteristics were further tested using the Kirby-Bauer diffusion method. Results showed that the soap met physical requirements, exhibiting a liquid texture, gray color, vanilla aroma, pH 7.08, viscosity of 1370 mPas, specific gravity of 1.01 g/mL, and foam height of 2 cm. The neutral-pH VCO soap demonstrated antibacterial activity against both S. aureus and E. coli. Statistical analysis using the Mann-Whitney test yielded an Asymp.Sig value of 0.083, indicating no significant difference between the antibacterial effects, suggesting broad antibacterial coverage. These findings support the potential of VCO soap for daily hygiene.